1995
DOI: 10.3171/jns.1995.83.6.1092
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic pituitary adenoma occurring in the interpeduncular cistern

Abstract: Intracranial ectopic pituitary adenoma occurs most frequently in the suprasellar cistern, usually in continuity with the pituitary stalk. Such tumors probably originate from cells of the pars tuberalis located above the diaphragma sellae or from aberrant anterior pituitary cells of the pituitary stalk. The authors report the case of a 37-year-old woman with Cushing's syndrome caused by an ectopic pituitary adenoma of unique location: the tumor was separate form the pituitary stalk and confined within the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 18 publications
0
13
1
1
Order By: Relevance
“…Regarding Cushing's disease due to corticotropinomas, the ratio of circulating ACTH (pg/ml by IRMA) to cortisol (mg/dl) was found to be 2.4 to 2.6 or 5.1 to 5.5 in cases of microadenoma or macroadenoma, respectively [30]. Based on this finding, the present case [7.25 to 12.1] and the other three [8.08, 12.0 and 8.0] out of 16 EAPA cases documented (see Table 1) were shown to have relatively high ratios of ACTH (pg/ml) to cortisol (mg/dl) com- pared to common Cushing's diseases, although these three cases, unlike our case, were reported to have completely overt Cushingoid features including moon face, truncal obesity, skin striae, pigmentation and atrophy, cervicodorsal hump, hypertension and diabetes mellitus [4,13,15]. Although the discrepancy of clinical symptoms and endocrine profile could be related to the individual sensitivity to cortisol, it is also possible that an aberrant less-active ACTH molecule exists in the plasma of these EAPA patients [31].…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…Regarding Cushing's disease due to corticotropinomas, the ratio of circulating ACTH (pg/ml by IRMA) to cortisol (mg/dl) was found to be 2.4 to 2.6 or 5.1 to 5.5 in cases of microadenoma or macroadenoma, respectively [30]. Based on this finding, the present case [7.25 to 12.1] and the other three [8.08, 12.0 and 8.0] out of 16 EAPA cases documented (see Table 1) were shown to have relatively high ratios of ACTH (pg/ml) to cortisol (mg/dl) com- pared to common Cushing's diseases, although these three cases, unlike our case, were reported to have completely overt Cushingoid features including moon face, truncal obesity, skin striae, pigmentation and atrophy, cervicodorsal hump, hypertension and diabetes mellitus [4,13,15]. Although the discrepancy of clinical symptoms and endocrine profile could be related to the individual sensitivity to cortisol, it is also possible that an aberrant less-active ACTH molecule exists in the plasma of these EAPA patients [31].…”
Section: Discussioncontrasting
confidence: 41%
“…1A and B). On her endocrine examinations, plasma ACTH level was markedly increased (196 to 280 pg/ml; normal, 9-52) but the serum cortisol level was not remarkable (23 to 27 mg/dl; normal [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Daily secretion of ACTH and cortisol lacked the normal circadian rhythm (Fig.…”
Section: Case Reportmentioning
confidence: 99%
“…It has been reported that pituitary adenomas rarely occur at a site in close proximity to but not in direct contact with the pituitary gland. The sites of these ectopic parasellar pituitary adenomas include the suprasellar region [1,7,10,14,15,20,21,29,30], the sphenoid sinus [11,13,27] and other intracranial regions [17,28]. Interestingly, a relatively large proportion of these ectopic pituitary adenomas consists of ACTH-secreting adenomas [1,7,11,17,20,21,27,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Ele prejudica o transporte da dopamina para os lactotrofos normais e resulta em hiperprolactinemia leve a moderada (< 200 ng/ml) [25][26][27] . Entretanto, Smith e Laws colocaram em dúvida o efeito de secção da haste e hipotetizaram que o fator mais provável fosse o aumento da pressão intra-selar 26 .…”
Section: Discussionunclassified